2012
DOI: 10.1007/s10545-012-9481-2
|View full text |Cite
|
Sign up to set email alerts
|

Enzyme replacement therapy for mucopolysaccharidosis VI: long‐term cardiac effects of galsulfase (Naglazyme®) therapy

Abstract: Characteristic cardiac valve abnormalities and left ventricular hypertrophy are present in untreated patients with mucopolysaccharidosis type VI (MPS VI). Cardiac ultrasound was performed to investigate these findings in subjects during long-term enzyme replacement therapy (ERT) with recombinant human arylsulfatase B (rhASB, rhN-acetylgalactosamine 4-sulfatase, galsulfase, Naglazyme®). Studies were conducted in 54 subjects before ERT was begun and at specific intervals for up to 96 weeks of weekly infusions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
2
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 25 publications
7
48
2
2
Order By: Relevance
“…Whilst long-term treatment has been shown in studies to reduce progression and morbidity (109), currently funding all 10 patients in Lithuania with this condition would represent 17% of the total in-patient budget for medicines and medical aids and 3% of total reimbursed ambulatory care pharmaceutical expenditure. Pressure is being placed on the Ministry of Health and Health Insurance Fund to reimburse galsulfase for these patients despite concerns with its value.…”
Section: Iv) New Medicines For Orphan Diseasesmentioning
confidence: 99%
“…Whilst long-term treatment has been shown in studies to reduce progression and morbidity (109), currently funding all 10 patients in Lithuania with this condition would represent 17% of the total in-patient budget for medicines and medical aids and 3% of total reimbursed ambulatory care pharmaceutical expenditure. Pressure is being placed on the Ministry of Health and Health Insurance Fund to reimburse galsulfase for these patients despite concerns with its value.…”
Section: Iv) New Medicines For Orphan Diseasesmentioning
confidence: 99%
“…An analysis of pooled data from the clinical trial program showed improvement in pulmonary function tests and growth velocity in patients (n=56, mean age approximately 12 years, range 5 to 29 years) who received ERT for up to 240 weeks [Decker et al, 2010; Harmatz et al, 2010]. Similarly, long-term ERT of up to 96 weeks reduced intraventricular septal hypertrophy and prevented progression of cardiac valve abnormalities in patients <12 years of age [Braunlin et al, 2012]. While the clinical trials and extension studies suggest significant clinical benefit of galsulfase treatment in MPS VI, the Resurvey Study provides information on the long-term effects of galsulfase treatment (ie, up to mean 6.8 years) on the natural progression of MPS VI.…”
Section: Introductionmentioning
confidence: 99%
“…The GAG levels remained between 6 and 10 mg/mmol of creatinine up to the time of writing, above the normal values of <4 mg/mmol of creatinine (Braunlin et al 2013).…”
Section: Resultsmentioning
confidence: 70%
“…In particular, the left ventricular hypertrophy and functional abnormalities of the mitral and aortic valves are progressive in individuals who are not treated (Braunlin et al 2013). These abnormalities are stabilized by galsulfase treatment (Brands et al 2013;Giugliani et al 2014).…”
Section: Discussionmentioning
confidence: 99%